Bone regeneration by bioactive glass fibrous threads and glass beads: Narrative review - Akhtar, Ramsha; Sara Bano; Akhtar, Muhammad Rohail; Waleed Ishaq; Masood, Sabeen; Chaudhary, Muhammad Aamir Ghafoor; Rehan Ahmed (Journal of the Pakistan Medical Association, 2025)
Before the emergence of biomedical engineering, organ transplantation was considered the ideal treatment option for survival. Still, with the advent of bioactive materials, regenerative medicine was revolutionized by utilising the basic knowledge of repairing soft and hard tissues. Bioactive glass fibres possess a large surface area and provide efficient cellular attachment, while micro-spherical beads can be used as a potent drug delivery and protein vehicle. According to the composition, they are categorised as silicate, phosphate, and borate bioglasses. Their mechanism begins while in contact with body fluids, and results in an ionic interchange and formation of a hydroxyapatite layer at the implantation site. Bioglasses have several applications in regenerative medicine and dentistry, like bone graft surgeries after tumour resections, osteomyelitis and tibial fracture rehabilitations, craniofacial, pulmonary, cardiac, and skin surgeries. They are also widely used in various operative dentistry and paediatric dental procedures. Key Words: Bioglass 45s5, Bioactive glass S53P4, Microspheras, NovaMin, Osteoconduction, Osteointegration, Growth factors.